Effect of Stabilization Exercise Improve Balance in Joint Degenerative Pain - Nuraini Noviati; Muthiah Munawaran; Tabita Dwi Cahyani; Kesit Ivanali (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2023)
Increasing life expectancy and sedentary lifestyle in the elderly have an impact on physical changes, especially degenerative joint disease. Exercise is a modality that can provide physiological and therapeutic effects so that it can prevent, treat, and improve the quality of health. However, to find an exercise design that has the desired therapeutic effect requires a long journey and in-depth study. Many recent studies have shown that exercise initiates the secretion of proteins and tissue regeneration hormones which are very necessary for anti-aging in the elderly. The purpose of this study is to further enrich the exercise design which can be used as a reference for the high-risk elderly population and the elderly in general so that the quality of life and life expectancy are getting longer. The research method used pre and post design experimental studies through the purposive sampling technique method which was divided into 4 groups consisting of the control group, experimental group 1 and experimental group 2 which were carried out in August-October 2022 at Balai Warga RT 08 Kembangan Village, West Jakarta. Samples that met the inclusive and exclusion criteria were obtained by 18 respondents. To determine the range of motion and balance function assessment, the sample was measured with a range of motion and balance test instrument. Data were analyzed using a paired sample t-test to determine the effect of stabilization exercises on joint motion and balance function. Statistical test results p=0,001, (p<0,05) experimental first group and p=0,011, (p<0,05) experimental second group showed that there was a significant difference in the experimental groups 1 and 2 but there was no difference in the balance function p=0,414, (p>0.05). The conclusion is that stabilization exercises affect the range of motion in degenerative joint pain.